Notes on the identity of two Indian species of Lindernia sensu stricto (Linderniaceae), and lectotypification of the name L. srilankana - Prasad, Managvayal Govindan; Sunojkumar, Purayidathkandy (Phytotaxa, 2018)
The taxonomic identity of two Indian species of Lindernia s. str. is revised and updated. Thus, the following names at the species rank are reduced to synonymy of what follows them in parenthesis viz. L. calemeriana (L. srilankana) and L. parviflora (L. dubia). Lectotype of L. srilankana is also designated for the first time.